Gross exports versus value added exports: Determinants and policy implications for manufacturing sectors in selected cee countries - Magdalena Olczyk; Aleksandra Kordalska (Gdańsk University of Technology, Faculty of Management and Economics, 2016)
The main objective of this paper is to assess the impact of selected determinants on both exports in value added and exports in gross terms for seven CEE economies, based on 13 manufacturing subsectors and for the period 1995-2011. The results of the analysis show a substantial decrease in domestic value added in a majority of the countries, especially in medium-high- and high-tech industries. For the seven CEE countries the impact of the main determinants (except vertical specialisation) are fairly similar when exports are measured in value added or in gross terms. The results indicate a greater impact of labour productivity and highly skilled employees on generating domestic value added in the manufacturing sector. CEE countries do not achieve comparative advantages of a capital-intensive nature in exports of manufactured products. Additionally, manufacturing in CEE countries does not serve a 'carrier function' for services to contribute to a country's export performance.
Keywords: C23; F12; F14; F40; L60; 330; gross exports; value added exports; CEE economies; manufacturing